2022
DOI: 10.3892/etm.2022.11595
|View full text |Cite
|
Sign up to set email alerts
|

Response to immunotherapy in a patient with advanced epithelioid sarcoma of adrenal gland: A case report

Abstract: Epithelioid sarcoma (ES) is a rare and highly invasive soft tissue malignant tumor with uncertain histogenesis. The localization of ES in the adrenal gland is rather unusual. The present study reported a case of stage IV ES in the adrenal gland of a 28-year-old male. The tissue biopsy of adrenal and lung lesions revealed epithelioid cells. Immunohistochemistry indicated that the tumor cells were strongly positive for cytokeratin (CK)8, CK, epithelial membrane antigen (EMA), CD34 and programmed cell death prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Case reports of the efficacy of pembrolizumab in advanced ES in adults have also been published. Pembrolizumab was used in the second line of palliative therapy, after chemotherapy with doxorubicin-ifosfamide [77]. In the study of nivolumab, a 24-year-old male ES metastatic lung patient had PR after 4 immunotherapy cycles, but the response was not durable as the patient progressed after the next 4 cycles [78].…”
Section: Systemic Therapies In Advanced Epithelioid Sarcomamentioning
confidence: 99%
“…Case reports of the efficacy of pembrolizumab in advanced ES in adults have also been published. Pembrolizumab was used in the second line of palliative therapy, after chemotherapy with doxorubicin-ifosfamide [77]. In the study of nivolumab, a 24-year-old male ES metastatic lung patient had PR after 4 immunotherapy cycles, but the response was not durable as the patient progressed after the next 4 cycles [78].…”
Section: Systemic Therapies In Advanced Epithelioid Sarcomamentioning
confidence: 99%
“…With regard to immunotherapy using immune checkpoint inhibitors (ICIs), there have been some case reports demonstrating a response ranging from partial remission to complete remission. These case reports used anti-PD1 ICIs such as pembrolizumab or nivolumab, or anti-CTLA-4 ICIs such as ipilimumab [31,32]. However, another retrospective analysis from a tertiary care center in India found that immunotherapy in two patients did not have any objective response [33].…”
Section: Epithelioid Sarcoma Of the Spinementioning
confidence: 99%